Chile : Technical Assistance Report-Introducing and Institutionalizing Spending Reviews. (IMF Staff Country Reports; Country Report, 2019)
This technical assistance report on Chile focuses on introducing and institutionalizing spending reviews (SR). The Chilean government has announced its commitment to achieving its fiscal target and containing expenditure growth. This report proposes a SR framework with targeted reviews conducted on an annual rolling basis, combined with a periodic comprehensive review at most once every four years. Both types of reviews include targets to identify savings options. Targeted reviews focus on a limited predefined review topic or area and on value for money and efficiency. Comprehensive reviews do not have any predefined review topics; they undertake an unconstrained search for the best saving options. The report sets out a four-stage process for conducting an SR, which would start in September and have final saving decisions made in April or May of the following year. The government will need to announce the topic for the first full targeted review to Congress in September 2019. This review will be conducted in late 2019 and early 2020; the results will be ready in April 2020 in time for incorporation into the process for the 2021 budget.